From dislocation nucleation to dislocation multiplication in ceramic nanoparticle. Issue 6 (3rd June 2021) - Issa, Inas; Joly-Pottuz, Lucile; Amodeo, Jonathan; Dunstan, David J.; Esnouf, Claude; Réthoré, Julien; Garnier, Vincent; Chevalier, Jérôme; Masenelli-Varlot, Karine
Abstract : Magnesium oxide nanocubes are compressed along the [001] direction in situ in the transmission electron microscope. Incipient plasticity in the smaller samples is characterized by the nucleation of few 1 / 2 < 110 > { 110 } dislocations while a larger number of line defects is observed in larger nanocubes. Yield and flow stresses scattered stochastically above a minimum value varying as the inverse of the sample size. The upper bound is given by the reduced number of dislocation sources. Such size-dependent behaviour is justified by a detailed statistical analysis and is fully explained by the deformation mechanism. GRAPHICAL ABSTRACT: UF0001